1995
DOI: 10.1007/bf03347836
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of growth hormone, insulin-like growth factor-I and prolactin in normal, growth retarded and anencephalic human fetuses

Abstract: We measured growth hormone (GH), insulin-like growth factor-I (IGF-I), and both total and glycosylated prolactin (PRL) levels in 131 blood samples obtained by cordocentesis in normal and abnormal fetuses from 19 to 40 weeks of gestation. In normal fetuses, IGF-I and PRL levels showed a positive correlation and GH a negative correlation with gestational age. A negative relation between GH and IGF-I levels was observed, while PRL did not show any correlation with both GH and IGF-I concentrations. IGF-I increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…In contrast to the report of Arosio et al [20] we found no correlation between GH levels and IGF-I levels. These discrepancies could stem from the pulsatile nature and the very high level of GH secretion in the neonate, with marked changes in GH levels [16].…”
Section: Complementary Resultscontrasting
confidence: 57%
“…In contrast to the report of Arosio et al [20] we found no correlation between GH levels and IGF-I levels. These discrepancies could stem from the pulsatile nature and the very high level of GH secretion in the neonate, with marked changes in GH levels [16].…”
Section: Complementary Resultscontrasting
confidence: 57%
“…First, this pattern of secretion may be an additional component of the altered somatotrophic axis observed in growthrestricted fetuses. Indeed, as previously described, plasma GH levels in cord blood were higher in IUGR fetuses than in normal fetuses and negatively correlated with birth weight, probably as a result of the reduced IGF-I levels present in this pathological condition (22,23). Therefore, it is likely that low IGF-I associated with intrauterine growth restriction may induce ghrelin overproduction, although the feedback mechanisms regulating ghrelin secretion are still poorly understood.…”
Section: Discussionmentioning
confidence: 70%
“…Results from measurements of IGF-I in serum of fetuses and preterm or term newborn infants have been more variable, as some groups find no difference in serum IGF-I concentrations between the male and female gender (6,10,13,15) and others report higher IGF-I in girls than boys (41,42). Reasons for this gender difference are not clear, but it has been suggested that differences in sex steroids could influence the secretion of IGF-I in utero (43).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for IGF-I are found in various tissues early in gestation (3), and fetal tissues seem to have enhanced sensitivity to IGF-I compared with later in life (4). Using cordocenteses, it has been possible to determine the "normal" range of IGF-I in fetal serum and to define a positive correlation between serum concentration of IGF-I and gestational age (5)(6)(7)(8)(9)(10). IGF-I levels are similar in arterial and venous cord serum, suggesting a fetal origin (1).…”
mentioning
confidence: 99%